2018
DOI: 10.1038/s41598-018-34881-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electronic and magnetic properties of MnxGa/Co2MnSi (x = 1, 3) bilayers

Abstract: Directly coupled hard and soft ferromagnets were popularly used as the hybridized electrodes to enhance tunnel magnetoresistance (TMR) ratio in the perpendicular magnetic tunnel junction (pMTJ). In this paper, we employ the density functional theory (DFT) with general gradient approximation (GGA) to investigate the interfacial structure and magnetic behavior of tetragonal Heusler-type MnGa (MG)/L21-Co2MnSi (CMS) Heusler alloy bilayers with the MnGa being D022-MnGa alloy (Mn3Ga) and L10-MnGa alloy (MnGa). The M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Different theoretical approaches have reported T C for L2 1 CMS as compared in Table II; [60,61], random-phase approximation (RPA) [60,62], and Monte Carlo (MC) simulation [63,64]. Among the MFA studies, reported results vary from 857 to 1162 K [57,60,61,65]. This may be caused by differences in computing exchange interactions, whose summation is required to calculate the T C , and/or in the DFT implementation.…”
Section: A Perfectly Ordered L2 1 Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Different theoretical approaches have reported T C for L2 1 CMS as compared in Table II; [60,61], random-phase approximation (RPA) [60,62], and Monte Carlo (MC) simulation [63,64]. Among the MFA studies, reported results vary from 857 to 1162 K [57,60,61,65]. This may be caused by differences in computing exchange interactions, whose summation is required to calculate the T C , and/or in the DFT implementation.…”
Section: A Perfectly Ordered L2 1 Structurementioning
confidence: 99%
“…The GGA and GGA+U methods were used in Refs. [65] and [57], respectively. Despite the differences in the T C of MFA results, we can see that the T C obtained from our DLM method shows the same magnitude and agrees well in particular with Ref.…”
Section: A Perfectly Ordered L2 1 Structurementioning
confidence: 99%
See 1 more Smart Citation
“…20 Wang et al reported that the hybrid of high purity SiC-NWs with PEDOT:PSS obtained a high PF of 67.7 mW m À1 K À2 . 21 Recently, SnSe as a p-type TE material with an ultrahigh ZT of 2.6 AE 0.3 was reported by Zhao et al 22 and has shown prominent TE properties due to its high PF and ultralow k (ref. [23][24][25] and has been a promising composite candidate with non-toxic and lower cost.…”
Section: Introductionmentioning
confidence: 99%
“…Co 2 MnSi is reported as 985 K, although MFA shows the T C is about 1170 K [45,46]. In case of IrCrMnZ Heusler alloys, T C are very high.…”
mentioning
confidence: 98%